2017
DOI: 10.3389/fpsyg.2017.01539
|View full text |Cite
|
Sign up to set email alerts
|

Letter-Sound Knowledge: Exploring Gender Differences in Children When They Start School Regarding Knowledge of Large Letters, Small Letters, Sound Large Letters, and Sound Small Letters

Abstract: This study explored whether there is a gender difference in letter-sound knowledge when children start at school. 485 children aged 5–6 years completed assessment of letter-sound knowledge, i.e., large letters; sound of large letters; small letters; sound of small letters. The findings indicate a significant difference between girls and boys in all four factors tested in this study in favor of the girls. There are still no clear explanations to the basis of a presumed gender difference in letter-sound knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 37 publications
3
32
1
2
Order By: Relevance
“…Whilst some biological accounts have been put forward (e.g., Burman, Bitan, & Booth, 2008;Halpern et al, 2007), most recent research implies sociocultural factors account for gender differences in reading and mathematics. For example, it has been suggested that during the preschool years, girls are likely to have more reading experience than boys because they are more motivated to read and mothers talk more to daughters than sons (Sigmundsson, Eriksen, Ofteland, & Haga, 2017), which supports the acquisition of oral language processing skills that are critical for learning to read (Nation & Snowling, 2004). Furthermore, Spelke (2005) argued that the composition of formal mathematics tests may favour boys over girls and sociocultural factors in the preschool environment in Kenya have been suggested to differentially influence the early acquisition of numerical concepts in boys and girls (Ngware, Ciera, Abuya, Oketch, & Mutisya, 2012).…”
mentioning
confidence: 99%
“…Whilst some biological accounts have been put forward (e.g., Burman, Bitan, & Booth, 2008;Halpern et al, 2007), most recent research implies sociocultural factors account for gender differences in reading and mathematics. For example, it has been suggested that during the preschool years, girls are likely to have more reading experience than boys because they are more motivated to read and mothers talk more to daughters than sons (Sigmundsson, Eriksen, Ofteland, & Haga, 2017), which supports the acquisition of oral language processing skills that are critical for learning to read (Nation & Snowling, 2004). Furthermore, Spelke (2005) argued that the composition of formal mathematics tests may favour boys over girls and sociocultural factors in the preschool environment in Kenya have been suggested to differentially influence the early acquisition of numerical concepts in boys and girls (Ngware, Ciera, Abuya, Oketch, & Mutisya, 2012).…”
mentioning
confidence: 99%
“…Early reading development involves learning how to map letters with speech sounds (Sigmundsson, Eriksen, Ofteland, & Haga, 2017;Sigmundsson, Haga, Ofteland, & Solstad, 2020), and experience with reading words causes reading to eventually become automatic and effortless (Ehri, 2005). Adults and children's reading differ in terms of reading experience, and dorsal stream processing might be more relevant in children because their reading is more demanding of attention.…”
Section: Discussionmentioning
confidence: 99%
“…The relative test-retest reliability of the test-battery was estimated using ICC (2, 1) (Shrout and Fleiss, 1979 ). The results were indicative of good reliability for individual test item scores, with ICCs between test and retest scores ranging from 0.985 to 0.992 (mean age 6.05 years, SD 0.28) in Norwegian children ( N = 20) (Sigmundsson et al, 2017a ).…”
Section: Methodsmentioning
confidence: 98%
“…Letter-sound knowledge has been found to be crucial for later reading development (National Reading Panel, 2000 ; Piasta and Wagner, 2010 ; Hulme et al, 2012 ) and also shown to be the best predictor of children's future spelling and reading abilities (Scarborough, 1998 ; Hammill, 2004 ; Schatschneider et al, 2004 ). Research indicates a significant difference that favors girls, in letter-sound knowledge among Norwegian school-aged children (Sigmundsson et al, 2017a ). However, research on gender differences in letter-sound knowledge is still limited (Dodd and Carr, 2003 ) and little is known on how these gender differences emerge in childhood.…”
Section: Introductionmentioning
confidence: 99%